Enhancing Green Ammonia Electrosynthesis Through Tuning Sn Vacancies in Sn-Based MXene/MAX Hybrids - Dai, Xinyu; Du, Zhen‑Yi; Sun, Ying; Chen, Ping; Duan, Xiaoguang; Zhang, Junjun; Li, Hui; Fu, Yang; Jia, Baohua; Zhang, Lei; Fang, Wenhui; Qiu, Jieshan; et al. (Nano-Micro Letters, 2024)
Renewable energy driven N2 electroreduction with air as nitrogen source holds great promise for realizing scalable green ammonia production. However, relevant out-lab research is still in its infancy. Herein, a novel Sn-based MXene/MAX hybrid with abundant Sn vacancies, Sn@Ti2CTX/Ti2SnC–V, was synthesized by controlled etching Sn@Ti2SnC MAX phase and demonstrated as an efficient electrocatalyst for electrocatalytic N2 reduction. Due to the synergistic effect of MXene/MAX heterostructure, the existence of Sn vacancies and the highly dispersed Sn active sites, the obtained Sn@Ti2CTX/Ti2SnC–V exhibits an optimal NH3 yield of 28.4 µg h−1 mgcat−1 with an excellent FE of 15.57% at − 0.4 V versus reversible hydrogen electrode in 0.1 M Na2SO4, as well as an ultra-long durability. Noticeably, this catalyst represents a satisfactory NH3 yield rate of 10.53 µg h−1 mg−1 in the home-made simulation device, where commercial electrochemical photovoltaic cell was employed as power source, air and ultrapure water as feed stock. The as-proposed strategy represents great potential toward ammonia production in terms of financial cost according to the systematic technical economic analysis. This work is of significance for large-scale green ammonia production. Highlights: 1 Sn-based MAX/MXene hybrids with abundant Sn vacancies, Sn@Ti2CTX/Ti2SnC–V, fabricated by controlled etching method, are demonstrated to be an excellent electrocatalyst for N2 electroreduction. 2 An economic “NH3 farm” has been developed based on Sn@Ti2CTX/Ti2SnC–V electrode, demonstrated by a commercial electrochemical photovoltaic cell, which may open a novel avenue for solar energy-driven synthesis of ammonia directly from air and water. 3 The potential of the “NH3 farm” was demonstrated by a systematic technical economic analysis.